Children undergoing early liver re‐transplantation for primary non‐function have improved survival. (25th June 2022) - Rogers, Michael E.; Delman, Aaron; Campbell, Kathleen; Miethke, Alexander; Tiao, Greg; Mullapudi, Bhargava; Bondoc, Alex
Abstract: Background: Primary non‐function (PNF) in the early post‐LT period in children leads to prolonged hospitalization, high graft loss, and significant mortality. However, there is a paucity of data available on the natural history of children relisted for LT due to PNF, including those who recover graft function and survive with their original allograft. Methods: We interrogated the United Network of Organ Sharing (UNOS) database for pediatric LT recipients who were relisted with a primary diagnosis of PNF from 2000 to 2020. Patients >21‐year‐old and multiple organ transplants were excluded. Logistic regression and Cox proportional hazard models were employed to identify risk factors for early re‐transplantation (within 30 days of relisting) and mortality after adjusting for baseline clinical characteristics. Results: One hundred and eight patients were relisted for LT for PNF during the study period. Twenty‐five patients survived beyond 30 days from relisting with their original LT, 76 underwent early re‐transplantation, and 7 did not survive. Having a high‐risk EBV mismatch (OR 2.03, 95% CI 0.66–6.27) and an elevated donor serum creatinine (OR: 2.19, 95% CI 0.54–8.84) were associated with increased odds of a patient requiring early re‐transplantation. Donor characteristics including age, final total bilirubin, final AST/ALT, and final serum sodium, as well as vasopressor use prior to procurement, were not associated with increased odds of early re‐transplantation ( p > 0.05). Operative characteristics including allograft type and cold‐ischemia time were also not associated with early re‐transplantation ( p > 0.05). Patients undergoing early re‐transplantation showed a trend toward improved 1‐year graft survival (69% vs 55%, p = 0.24). On multivariable Cox proportional hazards modeling, early re‐transplantation was associated with reduced risk of overall patient mortality compared to those who survived with their original LT (HR 0.27, 95% CI 0.12–0.67). Conclusion: Early re‐transplantation for PNF is associated with improved patient survival compared with patients who survive with their original LT.